Faktor Lingkungan yang berhubungan dengan kejadian Diare pada balita di Puskesmas Batang – Bantang Kabupaten Sumenep - Zakiyah Yasin; Elyk Dwi Mumpuningtias; Fitrul Faizin (Fakultas Ilmu Kesehatan, 2018)
Diarrhea is one of the health problems in developing countries, especially in Indonesia, both in urban and rural areas. Diarrhea is more dominant for toddlers because the immune system is still weak, so toddlers are very susceptible to the spread of the virus that causes diarrhea. Diarrhea disease is one of the diseases that need special handling and fast. If diarrheal diseases are not treated quickly, many complications will occur such as dehydration, hypovolemic shock, hypokalemia, seizures and malnutrition. This research uses analytical method with case control design. The sample in this research is partially infants suffering from diarrhea at Batang-Batang Public Health Center of Sumenep Regency as many as 20 infants. Sampling technique is simple random sampling. With case group (diarrhea) that is 10 infants diarrhea and control group (not diarrhea) that is 10 infants. This study uses primary data obtained from the results of questionnaires by respondents. The purpose of this research is to know the environmental factors related to the incidence of diarrhea in infants at Batang - Batang Public Health Center of Sumenep Regency. The results showed that most of the respondents in the case group (diarrhea) had an unsanitary environment of 70% and most of the control group (not diarrhea) had an unclean environment of 60%. The results showed that all case case respondents had diarrhea, 100% and almost all control group (not diarrhea) did not experience diarrhea, 80%. The conclusion in this research is environmental factors influencing the incidence of diarrhea in infants at Puskesmas Batang - Batang Sumenep regency 2018.